Optimal care pathways: A national policy to improve quality of cancer care and address inequalities in cancer outcomes. (September 2020) - Bergin, Rebecca J.; Whitfield, Kathryn; White, Victoria; Milne, Roger L.; Emery, Jon D.; Boltong, Anna; Hill, David; Mitchell, Paul; Roder, David; Walpole, Euan; te Marvelde, Luc; Thomas, Robert J.S.
Highlights: OCPs take a whole-of-pathway approach to improve outcomes for all Australians. OCPs are part of a history of cancer care policy reform in Australia. Government endorsement and stakeholder engagement aids implementation. Positive impacts of OCPs were found on care quality and cancer survival. Similar pathway policies may be considered in low and high resource countries. Abstract: Background: While Australia ranks highly in terms of cancer survival internationally, disparities in outcomes exist within the nation. To address this issue, Optimal Care Pathways (OCPs) were developed as a standard of care. Key principles of care, timeframes, quality standards and support needs were described in a seven-step pathway for 18 cancers. This paper discusses the potential value of pathways for care delivery, contextualises Australia's pathway policy approach and describes implementation strategies and early evidence of OCP impact. Methods: A literature review assessed international definitions and evidence of the utility of clinical care pathways. OCP implementation and evaluation approaches are described and case studies presented to demonstrate policy impact. Results: Australia's OCPs extend the traditional definition of care pathways by incorporating core principles and addressing the entire pathway from prevention to survivorship and end of life. In 2014−15, tumour-specific OCPs were developed drawing on the best-available evidence and stakeholder collaboration. After government endorsement, implementation tools and strategies were developed, with tailored roll-out in each of Australia's six states and two territories. Evaluation of implementation projects shows improved knowledge, awareness, and use of OCPs as tools for monitoring and improving performance. Population-based data confirm a positive relationship between care aligned with OCPs and cancer survival. Conclusion: OCPs are clinician- and consumer-built policy levers, supported by high-level government endorsement, to improve cancer outcomes for all Australians. Early findings suggest positive impacts on care quality and cancer survival. Low and high resource countries may consider similar pathway policies to improve cancer outcomes.